2022
DOI: 10.3390/jof8020179
|View full text |Cite
|
Sign up to set email alerts
|

Effect of γ-Heptalactone on the Morphology and Production of Monascus Pigments and Monacolin K in Monascus purpureus

Abstract: Monascus is used widely in Asian countries and produces various biologically active metabolites, such as Monascus pigments (MPs) and monacolin K (MK). In this study, the effect of γ-heptalactone on secondary metabolites and mycelial growth during Monascus purpureus M1 fermentation was investigated. After the addition of 50 μM γ-heptalactone, the yields of MPs (yellow, orange, and red) reached maxima, increased by 115.70, 141.52, and 100.88%, respectively. The 25 μM γ-heptalactone groups showed the highest yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…Monascus pigments and Monacolin K, the best‐known metabolites produced by Monascus , are widely used in food and medicines (Chaudhary et al, 2021), and numerous studies have focused on increasing the production of these valuable metabolites (He et al, 2021). The addition of various substances, such as tyrosol, farnesol, linoleic acid, rutin, La 3+ , γ ‐butyrolactone, genistein, and ascorbic acid, has been reported to enhance the production of Monascus pigments and Monacolin K (Erkaya et al, 2020; J. Huang et al, 2018; Z. Huang et al, 2019; H. Liu et al, 2021; Ouyang et al, 2021; Shi et al, 2022; Wei et al, 2022). Further investigation revealed that most of these exogenous molecules affect the secondary metabolism of Monascus and change the morphology of Monascus spores and mycelia by regulating relevant genes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Monascus pigments and Monacolin K, the best‐known metabolites produced by Monascus , are widely used in food and medicines (Chaudhary et al, 2021), and numerous studies have focused on increasing the production of these valuable metabolites (He et al, 2021). The addition of various substances, such as tyrosol, farnesol, linoleic acid, rutin, La 3+ , γ ‐butyrolactone, genistein, and ascorbic acid, has been reported to enhance the production of Monascus pigments and Monacolin K (Erkaya et al, 2020; J. Huang et al, 2018; Z. Huang et al, 2019; H. Liu et al, 2021; Ouyang et al, 2021; Shi et al, 2022; Wei et al, 2022). Further investigation revealed that most of these exogenous molecules affect the secondary metabolism of Monascus and change the morphology of Monascus spores and mycelia by regulating relevant genes.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation revealed that most of these exogenous molecules affect the secondary metabolism of Monascus and change the morphology of Monascus spores and mycelia by regulating relevant genes. Some of these inductive molecules are quorum‐sensing molecules that play various roles in the development and metabolism of Monascus (Erkaya et al, 2020; Z. R. Huang et al, 2018; Shi et al, 2022). Quorum‐sensing molecules are related to cell density and regulate morphology and secondary metabolite production in a variety of filamentous fungi (Palonen et al, 2017a, 2017b; Raina et al, 2010; Sorrentino et al, 2010; Wang et al, 2018; Williams et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Monascus spp. are industrial fungi used for food fermentation and pharmaceutical field since they can produce many beneficial metabolites, such as edible pigments, hypolipidemic compound monacolin K, blood pressure-lowering compound γ-aminobutyric acid, and highly active enzymes including glucoamylase, amylase, and esterase [2][3][4]. Recent archeology proved that the application of Monascus strain may be traced back to the Peiligang Culture Period over 8000 years ago in China.…”
Section: Introductionmentioning
confidence: 99%